Pengaruh Disiplin Terhadap Prestasi Kerja Pegawai di Kantor Kecamatan Bogor Utara Kota Bogor - Rizman Rifqie; Hesty Yulianti (STIE Binaniaga, 2008)
Cultural and behavioral changes in any activities associated with system changes people’s tives, man always has an important role in carrying out various activities of the organization because man is basically a thinker, implementer and supervisor in any activities that exist in every organization. White in the company we often hear the term human resource management, where manajemen human resources are an important asset fir the cimpany. Due to the absence of human resource manajemen activities, each organization will not be run in accordance with organizational objectives, in the calculation of linear regression analaysis can be concluded that the influence of labor discpline in bogor district office north was a positivie value to increase employee job peformance this can be proved frim the results of the analysis of linear regression equation is y = 0.46 x + 25.67 means that the functional relationship between the variables X (work discipline) with a variabel Y jon performance)) which means that the discpline of work increased by one unit for work performance will increase by 0.46. Based on the analysis that the author got from the questionnaire, stated that r = 0.57 close to positive one (+1), then the relationship between the variables of work discpline and work performance variables strong and positive. This is evidenced by the t test with t test in which this can result in thitung > ∏ able (3.18> 2.381) which means the correlation or relationship between the variables of work discpline and worl performance variables significan. The results obtained testing the hypothesis ho is rejected thitung > ∏ able it can be concluded that the variabele of work discpline and workperformance variables are related or korelasi. Berdasarkan analytical result obatained from the coefficient daterminants that unfluence the discipline of work on improvinf work permance has a very larga cotribution that is equal to 32, 49%